Kebijakan Pemerintah Nepal dalam Menanggulangi Perdagangan Organ Tubuh Manusia dari Nepal ke India - Shabrina, Izazi Nur; Putranti, Ika Riswanti; Farabi, Nadia (Journal of International Relations, 2018)
Since 2007, The Government of Nepal has began implementing Human Trafficking andTransportation Control Act 2064 to curb organ trafficking. In reality, the policy is unableto contain organ trafficking from Nepal to India. Therefore, by using explanative method,this research aims to to analyze the causes of the crime. In order to analyze the cause oforgan trafficking from Nepal to India, this research will use the public policyimplementation framework from Donald Van Horn and Carl Van Meter. This study findsthat organ trafficking from Nepal to India still occured because of the unfulfillment of thefollowing factors; standards and objectives, policy resources, interorganizationalcommunication and enforcement activities, characteristics of implementing agencies,economic, social and political condition and the disposition of implementers, therefore thepolicy cannot work accordingly.